Improvement Of Building Norms and Rules for the Construction of Buildings from Clay Soils - Tursunov N.S (Peerian Journals Publishing, 2022)
Despite the fact that residential and administrative buildings are being built in cities and villages from modern materials of concrete, reinforced concrete, steel and brick, more than 60% of the population of Central Asia, including Uzbekistan, still builds dwellings from local efficient and environmentally friendly clay material. In such developed countries as Germany, the USA, Great Britain, etc., priority is also given to environmentally friendly clay materials.
Keywords: concrete; reinforced concrete; became; brick